Paraplegia and intracranial hypertension following epidural anesthesia: report of four cases Paraplegia e hipertensão craniana após anestesia epidural: relato de 4 casos - Frederico A. D. Kliemann (Arquivos de Neuro-Psiquiatria)
Four patients who received epidural anesthesia presented sustained myelopathy; three of them had complete paraplegia and one a lumbo-sacral myelopathy with urinary retention. All four patients complained of very intense radicular pains immediately after the analgesic effect of Lidocaine was over. Two patients in whom lumbar puncture was done in the first 24 hours presented an aseptic meningitic reaction in CSF. Paraplegia completed in two to ten months in three patients and in two of them severe intracranial hypertension developped at this time. It is proposed that the disease runs a two-stages course, at least in some cases, characterized by an aseptic meningitis, followed, after a silent period of some months, by signs of adhesive spinal and intracranial arachnoiditis. Intracranial hypertension was controlled by ventriculo-peritoneal shunt; in two patients a transitory effect of intrathecal injections of methyl-prednisolone acetate was observed. Two patients recovered almost completely from paraplegia. Quatro pacientes que receberam anestesia epidural apresentaram mielopatia de longa evolução; em três ocorreu paraplegia completa e um apresentou uma síndrome medular lombo-sacra com retenção urinária. Todos os pacientes se queixaram de intensas dores radiculares imediatamente após a cessação do efeito analgésico da lidocaína. Dois pacientes apresentaram uma reação meningítica asséptica no líquido cefalorraqueano nas primeiras 24 horas. A paraplegia tornou-se completa em 2 a 10 meses após a anestesia; dois pacientes tiveram hipertensão craniana severa. Em alguns casos, senão em todos, esta afecção apresenta uma evolução em duas etapas, caracterizadas por meningite asséptica imediata, seguida, depois de um período silencioso de poucos meses, de sinais de aracnoidite adesiva espinal e intracraniana. A hipertensão intracraniana foi controlada por derivação ventriculo-peritoneal; em 2 pacientes houve melhora transitória pela administração de metil-prednisolona intratecal. Em dois pacientes houve recuperação quase completa da paraplegia.